(untitled) (Confluenţe Bibliologice, 2024)
This study is a synthesis of the research of French periodicals hold in the Scientific Library USARB Collection of Rare Documents. They include extremely rich and valuable materials, which can help to develop a significant work among students, academic staff for research and universal knowledge.